2020
DOI: 10.1108/ijoem-03-2019-0197
|View full text |Cite
|
Sign up to set email alerts
|

Does bank competition matter for performance and risk-taking? empirical evidence from BRICS countries

Abstract: PurposeThis study examines the relationship between banks' competition performance and risk-taking behavior concerning the impacts of bank size and the recent global financial crisis. The analysis empirically uses dynamic panel data from 1137 banks of the BRICS countries (i.e. Brazil Russia India China and South Africa) for the period 2000–2015.Design/methodology/approachDynamic panel generalized method of moments (GMM) has been used primarily to examine the effect of bank competition on performance and risk-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(49 citation statements)
references
References 104 publications
(235 reference statements)
2
47
0
Order By: Relevance
“…The recent studies on COVID-19 pandemic investigate predominantly the government interventions on stock market return [25][26][27]. The studies that examine the impact of the pandemic on bank performance (more specifically, the financial stability of banks) support the notion that during the financial crisis the responses of capital to risk-taking aptitude of banks is not similar to the normal economic conditions [27,28]. For example [29], finds that higher capital levels promote banks' financial stability by lessening the risk, and higher risk impedes the growth of capital.…”
Section: Introductionmentioning
confidence: 99%
“…The recent studies on COVID-19 pandemic investigate predominantly the government interventions on stock market return [25][26][27]. The studies that examine the impact of the pandemic on bank performance (more specifically, the financial stability of banks) support the notion that during the financial crisis the responses of capital to risk-taking aptitude of banks is not similar to the normal economic conditions [27,28]. For example [29], finds that higher capital levels promote banks' financial stability by lessening the risk, and higher risk impedes the growth of capital.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we try to find out the effect of bank size on credit risk in the context of Bangladesh. Other relevant studies (Moudud-Ul-Huq, 2019b, 2020; Zheng & Moudud-Ul-Huq, 2017) found that bank size is a significant determinant of risk. Another study conducted by Rahman et al (2015) in the context of Bangladeshi banks, found that large banks technically hold a lower amount of regulatory capital which is sometimes below the thresholds and absorb a higher level of risk.…”
Section: Variable Definitionmentioning
confidence: 95%
“…During 2008, the GFC and economic downturn increased the uncertainty and negatively affected the world economy (Moudud-Ul-Huq, 2020; Moudud-Ul-Huq Zheng, Gupta, Hossain, & Biswas, 2020). Based on the above discussion, we find that credit risk is the main cause of the GFC, which in turn might lead to serious liquidity problems to the firms and hence can go for bankruptcy.…”
Section: Hypotheses Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Equity percentage participation by the largest shareholder of the bank. +/- (Anderson & Fraser, 2000;Burkart et al, 1997;Gorton & Rosen, 1995;Iannotta, Nocera, & Sironi, 2007;Martínez & Ramírez, 2011) Bank Size (BS) Log of total assets _ (Bokpin, 2013;Moudud-Ul-Huq, 2020;Srairi, 2013;Su, 2010…”
Section: Definition Of Control Variablesmentioning
confidence: 99%